Tensile Strain Hardening Behavior of PVA Fiber-Reinforced Engineered Geopolymer Composites - Nematollahi, B.; Sanjayan, J.; Shaikh, Faiz (American Society of Civil Engineers (ASCE), 2015)
This paper is aimed to improve the mechanical properties (namely compressive and tensile strengths) of a recently developed fly ash-based engineered geopolymer composite (EGC) with relatively low-concentration activator combinations. In this regard, four different activator combinations (including two Na-based solutions and one K-based activator solution, and one lime-based activator combination in the form of powder) were used to develop the fly ash-based EGCs exhibiting strain hardening behavior under uniaxial tension. Randomly oriented short polyvinyl alcohol (PVA) fibers (2% v/v) were used to reinforce the relatively brittle low-calcium (Class F) fly ash-based geopolymer matrix. The matrix and composite properties of the developed fly ash-based EGCs [including workability of the fresh matrix, density, compressive strength, matrix fracture properties (comprising elastic modulus, fracture toughness, and composite crack tip toughness), and uniaxial tensile behavior] were evaluated. A counterpart conventional engineered cementitious composite (ECC) with a water-to-cement ratio corresponding to the activator solution to fly ash ratio of the EGCs was also made for comparison. Experimental results revealed that in fly ash-based EGCs, the use of Na-based activator combination composed of 8.0 M NaOH solution (28.6% w/w) and Na2SiO3 solution (71.4% w/w) with a SiO2/Na2O ratio of 2.0 is highly beneficial in terms of lower cost, higher compressive strength, higher matrix fracture properties, and superior uniaxial tensile behavior compared to the other three activator combinations.